2022
DOI: 10.1155/2022/1682147
|View full text |Cite|
|
Sign up to set email alerts
|

Cloud-Based Android Intelligent Voice and Enterprise Economic Statistics System Design

Abstract: The analysis of the current economic statistics system shows that the requirements for computing and storage capacity are relatively high. For the previous main controller, it is difficult to meet this basic requirement, but the application of cloud computing technology can solve this problem to a greater extent. Therefore, this paper designs a new economic analysis system based on cloud computing, which can enable small- and medium-sized enterprises to master the business information transmitted by customer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…First of all, an economic management system is built based on cloud computing technology, and the enterprise managers can know the economic flow of the enterprise through the system and, at the same time, play a monitoring role. The system was tested, and the experiments showed that the economic management system of the enterprise designed based on cloud computing technology substantially reduced the cost of enterprise communication [8]. Telegraphi, H. B.…”
Section: Ams 2010 Codes: 90b06 1 Introductionmentioning
confidence: 99%
“…First of all, an economic management system is built based on cloud computing technology, and the enterprise managers can know the economic flow of the enterprise through the system and, at the same time, play a monitoring role. The system was tested, and the experiments showed that the economic management system of the enterprise designed based on cloud computing technology substantially reduced the cost of enterprise communication [8]. Telegraphi, H. B.…”
Section: Ams 2010 Codes: 90b06 1 Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%